To the question on contact interaction of the flat stamp with semispace - Ткачук, Николай Николаевич; Ткачук, Антон Николаевич (Eastern-European Journal of Enterprise Technologies, 2010)
Interaction of a rigid punch with the elastic semispace is considered. A singular integral equation derived is solved by the method of discrete singularities. The parametrical analysis of model is carried out.